1988
DOI: 10.1063/1.340332
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for radiation resistance of InP solar cells

Abstract: Photovoltaic properties of InP solar cells and defect behaviors of InP single crystals irradiated with 1-MeV electrons have been studied in order to clarify the superior radiation resistance of InP solar cells compared to Si and GaAs solar cells. It is confirmed that the excellent radiation tolerance of the InP cells is originated from the room-temperature annealing and minority-carrier injection-enhanced annealing phenomena of major radiation-induced defects in InP. The main defects in InP induced by irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(42 citation statements)
references
References 22 publications
2
38
0
2
Order By: Relevance
“…This transformation should be associated with the formation of a complex between VP and doping impurities since the radiation hardness of InP increases with the doping concentration. [2,37] Therefore, a partial compensation of deep traps, originated from the photodegradation of CH3NH3 molecules, or their participation in the formation of recombination non-active defect complexes with proton-induced Frenkel defects reduces non-radiative recombination losses in the perovskite active layer. This is a reason for the unexpectedly observed enhancement of main photoelectric parameters Voc, FF and τ of the proton irradiated perovskite solar cell in comparison to the control solar cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transformation should be associated with the formation of a complex between VP and doping impurities since the radiation hardness of InP increases with the doping concentration. [2,37] Therefore, a partial compensation of deep traps, originated from the photodegradation of CH3NH3 molecules, or their participation in the formation of recombination non-active defect complexes with proton-induced Frenkel defects reduces non-radiative recombination losses in the perovskite active layer. This is a reason for the unexpectedly observed enhancement of main photoelectric parameters Voc, FF and τ of the proton irradiated perovskite solar cell in comparison to the control solar cell.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the difference in the number of atoms (three iodine atoms per one lead atom) and in atomic masses of lead and iodine atoms it is conceivable that the density of VI and Ii will be larger than that of VPb and Pbi in the analogy with InP where the radiation damage is mainly associated with the displacement of light weight phosphorus atoms. [2,37] Due to the ionic bounding nature of perovskite and its large dielectric constant the point defects VI, Ii and VPb form shallow traps with energy levels close to the conduction or valance bands. [22,38] This unique feature of hybrid organic-inorganic perovskites is the main reason why solution processed perovskite films with low structural perfection and many intrinsic defects possess a large diffusion length of photo-generated charge carriers and show extraordinary photovoltaic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Though a similar annealing profile to that for HD1 is observed, H4 shows a thresholdannealing temperatureof-10043 andcompleterecovery at 14o"c, a difference of 30°C higher than that of HD1 and significantly larger than the experimental error (4°C). The annealing temperature obtained for H4 coincides with values reported by other workers [2,9] and clearly shows that the defect HD1 is different f" defects H3 and H4. Figure 9 also shows the dependence of carrier concentration on annealing temperature, obtained from Schottky diodes measured at room temperature after for a fluence of 1 0l6 elanz.…”
Section: Defect Analysis Of Irradiated Inp Materialssupporting
confidence: 88%
“…In addition, it has been demonstrated that recovery of performance can be achieved under relatively benign annealing conditions [2,4]. However, the nature of the radiation induced defects, their influence on cell performance and their annealing characteristics are still at a fairly early stage of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…InP is also preferred, over Gallium Arsenide-based devices, for millimeter-wave sources and amplifiers due to its low noise and higher efficiency operations in the high frequency regime. It is also known that InP is a suitable material to make solar cells for terrestrial applications [2,3] due to its high radiation resistance [4] with high efficiency. InP-based ternary and quaternary compound semiconductors such as InGaP, InGaAs and InGaAsP provide several interesting opto-electronic properties suitable for multijunction solar cell applications [5].…”
Section: Introductionmentioning
confidence: 99%